Improved method for efficient imaging of intracellular Cl− with Cl-Sensor using conventional fluorescence setup - Friedel, Perrine; Bregestovski, Piotr; Medina, Igor (Frontiers in Molecular Neuroscience, 2013)
Chloride (Cl-) homeostasis is known to be fundamental for central nervous system functioning. Alterations in intracellular Cl- concentration ([Cl-]i) and changes in the efficacy of Cl- extrusion are involved in numerous neurological disorders. Therefore there is a strong need for studies of the dynamics of [Cl-]i in different cell types under physiological conditions and during pathology. Several previous works reported having successfully achieved recording of [Cl-]i using genetically encoded Cl-Sensor that is composed of the cyan fluorescent protein (CFP) and Cl--sensitive mutant of the yellow fluorescent protein (YFPCl). However all reported works were performed using specially designed setups with ultra-sensitive CCD cameras. Our multiple attempts to monitor Cl--dependent fluorescence of Cl-Sensor using conventional epifluorescence microscopes did not yield successful results. In the present work, we have analysed the reason of our failures and found that they were caused by a strong inactivation of the YFPCl component of Cl-Sensor during excitation of the CFP with 430 nm light. Based on the obtained results, we reduced 20-fold the intensity of the 430 nm excitation and modified the recording protocol that allows now stable long-lasting ratiometric measurements of Cl-Sensor fluorescence in different cell types including cultured hippocampal neurons and their tiny dendrites and spines. Simultaneous imaging and patch clamp recording revealed that in mature neurons, the novel protocol allows detection of as little as 2 mM changes of [Cl-]i from the resting level of 5-10 mM. We demonstrate also a usefulness of the developed [Cl-]i measurement procedure for large scale screening of the activity of exogenously expressed potassium-chloride co-transporter KCC2, a major neuronal Cl- extruder, that is implicated in numerous neurological disorders and is a target for novel therapeutical treatments.